Technology adoption and innovation of e-government in republic of Iraq - Faaeq, Munadil K.; Alqasa, Khaled; Al-Matari, Ebrahim Mohammed (Canadian Center of Science and Education, 2014)
Electronic government (EG) refers to a computer application employed in government activities and operations,where both government and the public are enabled to interact and transact online.The practicability of EG has not been largely explored in the context of Iraq, owing to the conflicting activities it has been experiencing in the past few years.Prior to EG adoption, variables have to be examined such as infrastructure, social factors,security, skills, users’ behavior etc. The present study aims at examining the related variables that could potentially bar the EG services adoption in Iraq with the help of the Unified Theory of Acceptance and Use of Technology (UTAUT).Three independent variables are examined namely effort expectancy, performance expectancy, and social influence – the influence of these variables on the EG services uses as the dependent variable is examined.The study proposes a quantitative examination of the EG services usage behavior with data gathered from Iraq.The study findings are then discussed.